ANALYSIS OF GEN Z PERCEPTION OF MOBILE BANKING OPERATIONAL RISKS OF SYARIAH BANKS (Case Study of Islamic Banking Students of UM Surabaya) - Ratih Puspitaningrum; Arin Setiyowati; Fatkur Huda (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to explore the perceptions of generation Z, especially students, towards the operational risks of mobile banking at Islamic banks. The research method used is qualitative with a case study approach, where data is collected through interviews with nine informants selected through purposive sampling techniques, namely Islamic Banking students of UMSurabaya who actively use mobile banking services at Islamic banks. Data validity is obtained through triangulation, and data analysis is carried out by data reduction, data presentation, and drawing conclusions. The results of the study show that the majority of informants assess this service positively because it is in accordance with Islamic principles, although there are concerns regarding technical risks and data security. This shows that the success of mobile banking services depends on the balance between Islamic principles and the quality of a system that is safe for users.